Diskripsi Status Balita Stunting - Ega Santiago Firlita Dewi Imron; Yuliasti Eka Purnamaningrum; Dwiana Estiwidani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
The percentage of nutritional status of stunting toddlers (short and very short) in Indonesia in 2013 is 37.2%. One of stunting effects is the growth disorder that will have an impact on the decline in the quality of human resources in the future. Kulon Progo Regency is one of districts included in the 100 districts in stunting prevention. This study aims at recognizing the developmental status of stunting toddlers in the Working Areas of Pengasih II Health Center in Kulon Progo Regency. Cross sectional approach is used for this research. The populations were 90 stunting toddlers who lived in Karangsari Village. The data were taken from Public Health Office in Kulon Progo, and the measurement directly used KPSP from 5 to 17 January 2019. The resuly of this study describes that most toddlers are male in 55.6%, economical status < UMK in 77.8%, exclusive breadfeeding status of 94.4%, middle school’s last education in 73.3%, mothers who did not work in 78.9%. The development status of the toddler is short, 53.3% of the development is appropriate, 36.7% is dubious and 1.1% is deviant. Toddlers are very short, 6.7% development is appropriate, 1.1% development is doubtful, and 1.1% development deviates. The conclusion of this study discovers that the developmental status of stunting toddlers in the Working Areas of Pengasih II Health Center in Kulon Progo Regency is appropriate if people pay attention on the other aspects such as giving exclusive breastfeeding, giving the stimulation by parents and participation in PAUD, and taking the last education for mothers.